Hotel Revenue Performance: Roles of Labor, Liquidity, and Governance Mechanism - Agung, Chris Petra; Inawati, Wahdan Arum; Anggita, Meidila (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
There is a remarkable contribution of hotel industries towards Indonesian GDP in the past few years. However, hotel business is vulnerable to uncertainty such as economic crisis, regulation changes, and pandemic. This vulnerability inevitably causes a decrease in hotels’ occupancy rate that would lead to lower revenue growth. This study aims to analyze three factors that represents these uncertainties namely labor cost, liquidity, and governance mechanism. The samples involved in this paper were hotel companies listed in Indonesia Stock Exchange in 2017-2022 period. Data is collected through published financial reports. Multiple regression is done by using SPSS version 21. The results showed that: (1) labor cost significantly and negatively affected hotel revenue growth. This finding indicates that labor cost is only one of components forming labor productivity while labor productivity has more determining power in increasing hotel revenue; (2) board of director size significantly and negatively affected hotel revenue growth. This finding indicates that there is higher chance of negligence to duties for board of director members who have more peers in comparison with those who have less; (3) liquidity did not significantly affect hotel revenue growth. This finding suggests hotel companies to allocate their cash and cash equivalents to other allocations that have more capability in generating revenue. Furthermore, the R square is 0,243 meaning that hotel revenue growth is 24,3% explained by labor cost and board of director size.